Analisis Soal Cerita pada Buku Matematika Siswa Kelas VII Jenjang SMP Kurikulum 2013 Berdasarkan Taksonomi Bloom - Eka Anggriana W; Abdul Karim; Eva Yuni Rahmawati (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The purpose of this study is to: find out the level of story questions in the Mathematics Student Book Grade VII Junior High School Level Curriculum 2013 Based on Bloom's Taxonomy. The place in this study is SMP Negeri 4 Parungpanjang, Bogor Regency, for the 2019-2020 school year. This research method uses a qualitative or descriptive method because it is carried out under natural conditions. The object of this research is a class VII student math book Revised Edition 2017 by Abdul Rahman As'ari, et al. The data collection method is carried out by means of documentation. The data analysis technique refers to the Bloom revised table of cognitive domains of Anderson and Krathwohl. The implementation of data validity uses 4 criteria, namely: (1) Degree of credibility, (2) Transferability, (3) Dependability, and (4) Certainty (confirmability). The results of the study show that those who contain the C1 category level 0%, those that contain the C2 category 4%, those that contain the C3 category 43%, those that contain the C4 category 24%, which contains the C5 category 16%, and which contains the C6 category 13%. The four dimensions of the cognitive process in question are the cognitive process "Understanding" / C-2, the cognitive process "Applying" / C-3, the cognitive process "Analyze" / C-4, the cognitive process "Evaluating" / C-5, and the cognitive process "Creating" / C-6. The suggestion for other researchers is to set the time when the research, because this research takes a long time. And it is also expected to choose a teacher who really understands Bloom's Taxonomy, and it is recommended to choose the right teacher because many teachers are busy (do not have free time)